2000
DOI: 10.1007/s002130050022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bupropion on nicotine craving and withdrawal

Abstract: Study results indicate that bupropion ameliorates some nicotine withdrawal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
192
7
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(216 citation statements)
references
References 24 publications
13
192
7
4
Order By: Relevance
“…The findings accord with growing evidence that antidepressants may be used to reduce affective distress following quitting smoking (Hall et al 1998;Shiffman et al 2000;Lerman et al 2002). Notably, fluoxetine produced a reduction in negative affect and a rise in positive affect.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings accord with growing evidence that antidepressants may be used to reduce affective distress following quitting smoking (Hall et al 1998;Shiffman et al 2000;Lerman et al 2002). Notably, fluoxetine produced a reduction in negative affect and a rise in positive affect.…”
Section: Discussionsupporting
confidence: 84%
“…Effects of antidepressants on positive affect are less understood (Zald and Depue 2001). Although Shiffman et al (2000) found that bupropion attenuated a decrease in positive affect in euthymic smokers during 72-h nicotine deprivation, Lerman and colleagues (2002) did not detect an effect of bupriopion on post-cessation positive moods.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since pharmacologically treating withdrawal improves treatment outcome for nicotine dependence (see Shiffman et al, 2000) and opiate dependence (Dole, 1988), we have conducted a series of laboratory studies testing the effects of medications on symptoms of marijuana withdrawal. Maintenance on two medications, the antidepressant, bupropion (Haney et al, 2001), and the mood stabilizer, divalproex (Haney et al, 2004), significantly worsened mood during marijuana withdrawal compared to placebo, suggesting that they would not show promise as treatment approaches.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…In the laboratory, marijuana withdrawal is alleviated by the resumption of marijuana smoking or by THC administration, demonstrating the pharmacological specificity of withdrawal (Haney et al, 1999b(Haney et al, , 2004Hart et al, 2002). Clinically, marijuana smokers report using marijuana to alleviate withdrawal symptoms (Budney et al, 1999), suggesting withdrawal contributes to relapse and the maintenance of marijuana use.Since pharmacologically treating withdrawal improves treatment outcome for nicotine dependence (see Shiffman et al, 2000) and opiate dependence (Dole, 1988), we have conducted a series of laboratory studies testing the effects of medications on symptoms of marijuana withdrawal. Maintenance on two medications, the antidepressant, bupropion (Haney et al, 2001), and the mood stabilizer, divalproex (Haney et al, 2004), significantly worsened mood during marijuana withdrawal compared to placebo, suggesting that they would not show promise as treatment approaches.…”
mentioning
confidence: 99%